UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII. A DI MTS AS'ADIYAH PUTRI PUSAT SENGKANG KABUPATEN WAJO - Hamid, Mutmainna; Mustamin; Raehana, Syarifa; Akil, M; Sudarmono , Muh Aidil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to comprehensively describe the strategies implemented by educators in increasing student learning motivation in the subject of Aqidah Akhlak in class VIII.A, MTs As'Adiyah Putri Pusat Sengkang, Wajo Regency. This study adopted a qualitative approach, with a primary focus on the role of teachers and student responses. Data collection methods included participant observation, semi-structured interviews, and documentation analysis. Data analysis was carried out through a series of systematic stages, namely data collection, data reduction, data presentation, and drawing conclusions based on empirical evidence. The results of the study indicate that teachers of the subject of Aqidah Akhlak have implemented various strategies designed to increase student learning motivation. These strategies include providing rewards as a positive stimulus, creating healthy academic competition between students, implementing periodic tests as a formative evaluation instrument, providing prizes as a form of appreciation for academic achievement, and implementing educational punishments as an effort to enforce discipline. Supporting factors in implementing this strategy include an adequate number of students, continuity of teaching staff from grades VII to IX, which allows for a deep understanding of student development, and teacher competence in designing engaging learning through the selection of appropriate methods and the formation of positive attitudes. Meanwhile, inhibiting factors include limited educational facilities and infrastructure, the influence of an unfavorable social environment, and a lack of family support in fostering student learning motivation.